Seqüências de (sibilante + consoante) no português de Belo Horizonte (Revista de Estudos da Linguagem, 2004)
This paper investigates cases of sound variation involving sequences of (sibilant + consonant) in Brazilian Portuguese (BP). Emphasis is given to the analysis of alveolar (sibilant + stop) sequences as in the word – festa [ÈfEsta] – and to the alveopalatal (sibilant + affricate)sequences – as in the word triste [ÈtRiStSi]. The cases of variation we will be dealing with involve the loss of the stop or the affricate where only the sibilant is manifested: festa ‘party ‘ [ÈfEsta] à [ÈfEsa]and triste ‘sad’ [ÈtRiStSi] à [ÈtRiSi]. This paper evaluates the role of phonetic properties as potential motivation for the variation:agreement of place of articulation and also agreement of voicing for the consonants in the sequence is considered. The fact that the sequences involved in the variation are related to a complex syllable pattern – that is, (coda-onset) – will also be explored. Some structural aspects which may condition the phenomena will be addressed:stress placement and the quality of the vowel which precedes the(coda-onset) sequence. It will be suggested that the lack of conditioning structural factors leads us to evaluate this case of variation within the Lexical Diffusion model (WANG, 1969). Lexical Diffusion appears to be the most appropriate approach to analyse the phenomena addressed in this paper, since it accounts for the .different behaviour of some structurally similar sequences. Finally,the paper indicates some aspects to be pursued in future research.